In patients with superficial vein thrombosis the inflammatory response is increased and related to the recanalization rate - Pavel Poredoš (Termedia Publishing House, 2019)
Introduction Little is known about pathogenetic mechanisms of superficial venous thrombosis (SVT). We aimed to investigate the systemic inflammatory response in the acute phase of SVT, the time course of inflammatory markers and involvement of inflammation in resolution of thrombus in SVT.